QUALITY OF EDUCATIONAL SERVICES AT MADRASAH TSANAWIYAH AL MUHAJIRIN KENDARI - Nurjannah; Yasin Saputra (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the quality of educational services at Madrasah Tsanawiyah (MTs) Al-Muhajirin by examining several dimensions of service quality, including reliability, tangibles, responsiveness, assurance, and empathy, in order to identify factors affecting student and parent satisfaction. This research employed a qualitative method with a phenomenological study approach. The informants in this study consisted of the principal, teachers, and parents of students. Data were collected through interviews, observations, and documentation. The data analysis process involved data collection, data reduction, data presentation, and conclusion drawing. To ensure data validity, the study applied source triangulation, technical triangulation, and member checking techniques. The findings indicate that the quality of educational services at MTs Al-Muhajirin has not yet fully met students’ and parents’ expectations. While responsiveness, assurance, and empathy were generally satisfactory, improvements are still needed in teacher reliability and the adequacy of educational facilities, particularly classrooms and library services. These findings suggest the need for continuous efforts to enhance overall service quality. The findings suggest that improving educational service quality requires strengthening teacher reliability, upgrading educational facilities, and enhancing student support services. The study also highlights the importance of continuous evaluation and stakeholder involvement in improving service quality and increasing student and parent satisfaction in Islamic educational institutions. This study contributes to the discourse on educational service quality in Islamic educational institutions by providing an in-depth phenomenological analysis of service dimensions at the madrasah level. The findings offer practical insights for improving educational service management to achieve greater student and parent satisfaction.